2020
DOI: 10.1111/1365-2664.13777
|View full text |Cite
|
Sign up to set email alerts
|

Crop pollination services: Complementary resource use by social vs solitary bees facing crops with contrasting flower supply

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Although several other bee species also contribute to pollination, researchers have focused on only a limited number of these to date, particularly the bumble bee (Bombus spp.) [19,20]. In comparison to wild bees alone, Greenleaf and Kremen observed that interactions between wild bees and honey bees doubled pollination rates and enhanced the prevalence of hybrid sunflowers by five-fold [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although several other bee species also contribute to pollination, researchers have focused on only a limited number of these to date, particularly the bumble bee (Bombus spp.) [19,20]. In comparison to wild bees alone, Greenleaf and Kremen observed that interactions between wild bees and honey bees doubled pollination rates and enhanced the prevalence of hybrid sunflowers by five-fold [21].…”
Section: Introductionmentioning
confidence: 99%
“…If the presence of honey bee hives decreased wild bee abundance on our study farms and honey bees were not visiting the strawberry or winter squash blooms, that could explain why we saw deficits in fruit count rather than a neutral or positive effect of honey bees. In fact, a recent study found that strawberries adjacent to mass-flowering oilseed rape received fewer honey and bumble bee visitations while the oilseed rape was blooming 59 . However, in contrast with our results, Bänsch and others found that farms benefitted from wildflower strips during mass oilseed rape blooms because the wildflower strips supported wild pollinators which stepped in to pollinate strawberries, replacing managed bees and protecting strawberry yields 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Across all plants, pollinator communities differed between the two successive years. We assume that these differences are due to factors such as population fluctuations and weather differences, as well as the availability of alternative food sources (Bänsch et al 2020, Osterman et al 2021). In the second observation year (2018), plants began to flower around two weeks later.…”
Section: Resultsmentioning
confidence: 99%